Ambulatory Impedance Cardiography The Systems and their Applications - Cybulski, Gerard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
(3y(BAmbulatory Impedance Cardiography(3y (Bgives the reader the necessary physical background of impedance cardiography (ICG) and currently available systems for hemodynamics holter monitoring. It compares ambulatory ICG and other clinically accepted methods through an updated state-of-the-art. The book is divided in 4 parts. In the first one, the importance of the analysis of the cardiac dynamics using the ambulatory monitoring technique is presented. The second part contains the description of foundations of ICG, the models used to describe the ICG technique and the description of available systems for ambulatory monitoring of cardiac hemodynamics. The third part is devoted to the validation of the ambulatory ICG method, the verification of the quality of long term ICG recordings and the discussion of the limitations of this technique. In the last part, some clinical and research applications of the ICG ambulatory monitoring are presented.s
Introduction -- Impedance Cardiography -- Ambulatory Impedance Cardiography -- Validation of the method -- Clinical and physiological applications of Ambulatory Impedance Cardiography -- Final conclusions and future directions.
Keywords: Engineering; Cardiology; Biophysics; Biological physics; Biomedical engineering; Engineering; Biomedical Engineering; Cardiology; Biophysics and Biological Physics; Electronic books